Linking ecosystems, habitats, and biodiversity: from the grand picture to the tiny details, and back - Ferdinando Boero (Advances in Oceanography and Limnology, 2022)
Natural sciences usually proceed through the analysis of facts that are then assembled into a general framework, often called a “theory”. I have tried here to assemble the “tiny facts” that I have uncovered in my career and to organize them into a holistic perspective. I have chosen to start from the “big picture”, i.e., the functioning of ecosystems, to focus then on details regarding the expression of biodiversity, from the role of life cycles in ecosystem functioning, to the way of assessing biodiversity based on the accurate knowledge of its evolution in time. The Historical Biodiversity Index allows to compare the potential biodiversity (all the species recorded from the studied habitat type) with the realized biodiversity (the species found by sampling in that habitat). The study of natural history might lead to unexpected ecological connections, such as the dynamics of plankton (the most important ecological phenomenon of the whole planet) and the composition of resting stage banks, or the keystone role of the interstitial fauna in determining the diversity of plankton. The oceanic realm is in three dimensions and must be considered as a volume rather than as an area. Living systems, though, change constantly and a fourth dimension (time) is crucial to understand their structure and function. The cells of ecosystem functioning, based on connectivity, are proposed as natural spatial units for both management and protection from human impacts.